(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2023)
Micro-businesses or those small productive units that are born, mostly in response to an immediate need of their owners to generate income, are businesses that from informality energize the market and the economy in general; Despite its importance, the vulnerability they face in the midst of crises is very significant, particularly since their adaptive capacity is severely limited. This document presents the analysis of the results obtained in the MD Micronegocios program during the year 2021 in the Nariño territory, whose purpose was to strengthen small productive units in the midst of the economic reactivation that the country was going through; Thanks to this support process, it was possible to impact more than 300 businesses, and from there to understand that customer segmentation, the construction of a value proposition, the increase in sales and retention, as well as the expansion of buyers are challenges that continually their owners must face, additionally, it was understood that technological tools, particularly the use of social networks, is an opportunity to build the response to this challenge, however, it is necessary to better prepare for it because for the most part, there is little knowledge about the management and administration of these platforms.